Mind, heart, and soul in the fight against poverty - Marshall, Katherine, 1947-; Keough, Lucy (World Bank e-Library., 2004)
"Mind, Heart, and Soul in the Fight against Poverty explores the diversity of collaboration between development and religious institutions. It includes a wide range of case studies from all over the world. The narratives cover community-level interventions in support of excluded populations: work on education, health, and HIV/AIDS prevention: restoration of communities after conflict, and global efforts to bring greater clarity and meaning to such challenges as poor country debt, HIV/AIDS, and employment. Recent decades of development experience have taught vital lessons about creative partnerships in the struggle against poverty. This book delves into these lessons stressing the centrality of faith to change in the human experience."--Jacket